Mind maps by the visually impaired as a support to the urban information design on the Web - Golin, Geisa; Nogueira, Ruth E.; Alexandre, Gabriela C.; Cabral, Josiane M. (InfoDesign, 2009)
To recognize the visually impaired is, interestingly, to break prejudices and get in touch with a reality that is at the same time quite common. The adaptation of the city to the different users that live in it is a right that is guaranteed by law, so nowadays it is crucial to consider urban accessibility as a strong parameter for urban projects. This article intends to understand the visually impaired’s city, its mental maps for the urban routes and the availability of this information generated by the visually impaired on the web; in other words, to bring information about the city of Florianópolis to other citizens, analyzed and verified by and for the visually impaired. The focus of this article is to consider the web accessibility standards, but not only those, it is also very important to recognize the user that is going to access them. The simple transcription of information from a regular website to an accessible website can be ineffective if we consider the way the concepts are developed and verified by this group of users.